PENGARUH CORPORATE GOVERNANCE DAN KINERJA KEUANGAN TERHADAP FINANCIAL DISTRESS (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2015-2019) - Puji Nurhayati (ITB AAS INDONESIA, 2022)
Financial distress is a condition of the company will face difficulties with the emergence of the company's financial decline even to the point of bankruptcy. The research aims to examine the influence of managerial ownership, institutional ownership, audit committee size, liquidity, and profitability on financial distress. The population of this study is a manufacturing company of 169 companies. The samples were taken using purposive sampling, so 25 company samples were obtained. Data analysis techniques use descriptive statistics, classical assumption tests, multiple linear regression analysis, hypothesis tests, and coefficients of determination. Based on the analysis of data obtained the conclusion that managerial ownership has no effect on financial distress, institutional ownership has no effect on financial distress, audit committee size affects financial distress, liquidity affects financial distress, and profitability has no effect on financial distress.